Ablation treatment of hepatocellular carcinoma: a bibliometric analysis - Song, Jianping; Zhang, Tingxiao; Wang, Jianlei; Liu, Yanfeng (Frontiers in Oncology, 2023)
Objective: Ablation is a common treatment for hepatocellular carcinoma (HCC). This study aimed to assess research trends in the ablation treatment of HCC using bibliometric analysis. Methods: Publications between January 1, 1993 and December 31, 2022 were retrieved from the Web of Science database. The bibliometrix package from R software, CiteSpace, VOSviewer and an online analytical platform were used for data analysis and plotting. Results: A total of 4,029 publications were retrieved from the Web of Science database between 1993 and 2022. The annual growth rate of publication numbers was 10.14%. China had the largest number of publications in the field of HCC ablation. China and the United States of America have the most notable cooperation. Sun Yat-sen University had the largest number of publications in the field of HCC ablation. The most relevant journals were Hepatology, Journal of Hepatology, Gastroenterology, and Radiology. High-frequency keywords mainly focused on “therapy,” “resection,” “radiofrequency ablation” and “survival”. Conclusions: With the increase in related publications, the research direction of ablation treatment of HCC is mainly focused on “therapy,” “resection,” “radiofrequency ablation” and “survival”, and the ablation treatment method has gradually changed from percutaneous ethanol injection to radiofrequency ablation and microwave ablation. Irreversible electroporation may become the main method of ablation therapy in the future.